2003
DOI: 10.1080/08990220310001622997
|View full text |Cite
|
Sign up to set email alerts
|

Decline of tactile acuity in aging: a study of body site, blood flow, and lifetime habits of smoking and physical activity

Abstract: Tactile acuity of 60 older subjects (> or = 65 years) and 19 younger subjects (18-28 years) was assessed by two-point gap thresholds at the upper and lower surfaces of the forefinger, at the upper and lower surfaces of the feet, and at the volar surface of the forearm. The older subjects were assigned to one of four groups of 15 subjects each, depending on reported lifetime habits of physical activity and smoking: (1) active smokers, (2) active nonsmokers, (3) inactive smokers, and (4) inactive nonsmokers. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(53 reference statements)
3
28
1
Order By: Relevance
“…Furthermore, research has shown that the sensitivity of the skin to such stimuli declines with ageing [7,8,9,10,11]. From the present study there is clear evidence that thermal sensitivity declines with ageing to both a cold Whilst the present study supports previous research, it also adds to our current knowledge about the decline in thermal sensitivity with ageing and how it differs between the two sexes.…”
Section: Effect Of Ageing and Sexsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, research has shown that the sensitivity of the skin to such stimuli declines with ageing [7,8,9,10,11]. From the present study there is clear evidence that thermal sensitivity declines with ageing to both a cold Whilst the present study supports previous research, it also adds to our current knowledge about the decline in thermal sensitivity with ageing and how it differs between the two sexes.…”
Section: Effect Of Ageing and Sexsupporting
confidence: 79%
“…Impaired cutaneous vascular function and delays in the sweating and shivering thresholds have been reported in age comparison studies [2,3,4,5,6]. Likewise, reduced thermal sensations in older adults have been reported, alongside a number of other tactile responses (touch, pressure and noxious thermal sensitivity) [7,8,9,10,11]. With an increasing ageing population and increased reports of climate change, understanding the age related changes in our ability to thermoregulate is vitally important.…”
Section: Introductionmentioning
confidence: 99%
“…The failure to find an association between exercise and tactile acuity is inconsistent with the blood flow hypothesis which theorizes that TC enhances tactile acuity in a non-specific manner by increasing peripheral blood flow; this null result is in accord with a large study by Stevens et al (2003) which found both cumulative exercise and current hours-per-week to be unrelated to tactile spatial acuity.…”
Section: Discussioncontrasting
confidence: 68%
“…In this case, tactile acuity should be associated with cumulative lifetime and/or current intensity of exercise in both the TC group and the control group since exercise is a potent modulator of peripheral blood flow (although a null correlation between exercise and tactile acuity has been previously reported (Stevens, Alvarez-Reeves, Mack, & Green, 2003).…”
Section: Introductionmentioning
confidence: 87%
“…The greater morphological changes and reduced numbers of Meissner's corpuscles seen in the hands of older manual workers and to a lesser extent, older males in general (Cauna 1956(Cauna , 1965, suggest that increased damage may occur to neuromuscular structures in high contact areas (Cauna 1965). Previous studies found no difference between sensory declines on the dorsal and ventral sides of the finger (Stevens et al 2003) and foot (Mitchell and Mitchell 2000) with age, and suggested increases in skin thickness (Mitchell and Mitchell 2000) and skin wear (Stevens et al 2003) did not contribute to sensory decline. However, in these studies, the skin of the palm was not investigated.…”
Section: Changes Across the Handmentioning
confidence: 99%